Emerging Therapeutic Options for the Management of COPD. Issue 7 (January 2013) - Reid, Debra J.; Pham, Nga T.
Chronic obstructive pulmonary disease (COPD) is the fourth leading cause of death worldwide and is projected to be the third by 2020. COPD is characterized by chronic airflow limitation caused by airway inflammation and parenchymal destruction that is usually progressive. Inhaled bronchodilators continue to be the mainstay of the current management of COPD. Safety and efficacy data of the recently approved medications including aclidinium, glycopyrronium, roflumilast, and indacaterol are reviewed here.